Domestic multinationals, foreign affiliates, and labour demand elasticities - Olivier N. Godart; Holger Görg; David Greenaway (Institute for the Study of Labor (IZA), 2012)
Using information on a panel of multinational firms operating in the United Kingdom from 1996 to 2005, we find that labour demand in domestic multinationals is less sensitive to labour cost changes than in foreign multinationals. This difference in the wage elasticity of labour demand persists even when we control for the skill intensity of firms or their level of intangible assets. This is in line with an interpretation that the provision of headquarter services in domestic multinational firms protects against strong fluctuations in labour demand. Overall, our results suggest that the wage elasticity of labour demand is about 40 percent lower in domestic than in foreign multinationals.
Keywords: F23; J23; J24; 330; labour demand elasticity; multinational firms; headquarter services; skill intensity; Multinationales Unternehmen; Arbeitsnachfrage; Lohn; Preiselastizität; Unternehmenszentrale; Schätzung; Großbritannien